Performance Audit of National Rural Health Mission in Andhra Pradesh - CAG of India (CAG of India, 2009)
In April 2005, Government of India (GOI) launched the National Rural Health Mission (NRHM) throughout the country with special focus on 18 States including Andhra Pradesh. The Mission aimed at providing accessible, affordable, effective and reliable healthcare facilities in the rural areas. The Mission also aimed at an architectural correction in the healthcare delivery system by converging seven other stand alone existing National Disease Control Programmes (NDCP2) of the Ministry of Health and Family Welfare. The performance audit of the implementation of NRHM in Andhra Pradesh had the following objectives: • Whether planning was designed at State, district and village levels to effectively meet the mission objectives for ensuring accessible, effective and reliable healthcare to rural population; • Whether public spending on health sector over the years 2005-09 increased to the desired level and assessment, release of funds in the decentralised set up and utilisation of funds released and accounting thereof was adequate; • Whether the Mission achieved capacity building and strengthening of physical and human infrastructure at different levels as planned and targeted; • Whether the systems and procedures of procurement and equipment were cost effective and efficient; and • Whether the performance indicators and targets fixed specially in respect of reproductive and child healthcare, immunization and disease control programmes were achieved.
For the Period 2005-06 to 2008-09